Slitrk1 is localized to excitatory synapses and promotes their development - Beaubien, François (Sci Rep, 2016)
Following the migration of the axonal growth cone to its target area, the initial axo-dendritic contact needs to be transformed into a functional synapse. This multi-step process relies on overlapping but distinct combinations of molecules that confer synaptic identity. Slitrk molecules are transmembrane proteins that are highly expressed in the central nervous system. We found that two members of the Slitrk family, Slitrk1 and Slitrk2, can regulate synapse formation between hippocampal neurons. Slitrk1 is enriched in postsynaptic fractions and is localized to excitatory synapses. Overexpression of Slitrk1 and Slitrk2 in hippocampal neurons increased the number of synaptic contacts on these neurons. Furthermore, decreased expression of Slitrk1 in hippocampal neurons led to a reduction in the number of excitatory, but not inhibitory, synapses formed in hippocampal neuron cultures. In addition, we demonstrate that different leucine rich repeat domains of the extracellular region of Slitrk1 are necessary to mediate interactions with Slitrk binding partners of the LAR receptor protein tyrosine phosphatase family, and to promote dimerization of Slitrk1. Altogether, our results demonstrate that Slitrk family proteins regulate synapse formation.